Acetyl Zingerone: A Photostable Multifunctional Skincare Ingredient That Combats Features of Intrinsic and Extrinsic Skin Aging - Thomas A. Meyer; William R. Swindell; Ratan K. Chaudhuri (MDPI AG, 2023)
The cumulative damage skin sustains from exposure to environmental stressors throughout life exerts significant effects on skin aging and cancer development. One of the main ways by which environmental stressors mediate their effects within skin is through induction of reactive oxygen species (ROS). In this review, we chronicle the multiple properties by which acetyl zingerone (AZ) as a skincare ingredient can benefit skin (1) by helping manage overproduction of ROS through multiple routes as an antioxidant, physical quencher and selective chelator, (2) by fortifying protection after UV exposure ends to prevent the type of epidermal DNA damage that correlates with development of skin cancer, (3) by modulating matrisome activity and nurturing the integrity of the extracellular matrix (ECM) within the dermis and (4) through its proficient ability to neutralize singlet oxygen, by stabilizing the ascorbic acid precursor tetrahexyldecyl ascorbate (THDC) in the dermal microenvironment. This activity improves THDC bioavailability and may blunt pro-inflammatory effects of THDC, such as activation of type I interferon signaling. Moreover, AZ is photostable and can sustain its properties during UV exposure, in contrast to α-tocopherol. All these properties of AZ translate into measurable clinical benefits to improve the visual appearance of photoaged facial skin and to strengthen the skin's own defenses against sun damage.